The Pengalaman Relaktasi Ibu Menyusui Pascaterinfeksi Covid-19 di Jadebotabek - Mia Ilmiawaty Saadah (Yayasan Pendidikan Medika Indonesia, 2022)
SARS-Cov-2 infection during the Covid-19 pandemic can lead to the cessation of breastfeeding however they may relactate after recovery. Relactation is the process of reintroducing breastfeeding to a child who had previously ceased. Breastfeeding is not just giving the breastmilk is an important reason why relactation is necessary. This descriptive phenomenological research aims to be able to find out the life experience (lived-experience) of breastfeeding mothers in Jakarta Greater Area in undergoing relactation after being infected with Covid-19. Data were obtained through in-depth interviews with 15 participants and analyzed using the Colaizzi’s method. There were seven emergent themes: 1) Indication, 2) Motivation, 3) Strategy, 4) Mother's emotions, 5) Support, 6) Breastfeeding information, and 7) Hope. This study demonstrates that relactation during a Covivirus-19 pandemic is achievable and practicable. Relactation is possible for all women, irrespective of educational level, working status, infant age, mother's age, parity status, and time after nursing was stopped as long as they get enough support. This study emphasizes the necessity for a relactation guide as a reference for breastfeeding mothers and health providers. Telemedicine, breastfeeding helpline, and homecare services are also needed through health facilities, both in terms of access and health expenditures for moms undergoing relactation. Moreover, given the magnitude of this support's impact on the efficacy of breastfeeding and relactation, it is vital to design breastfeeding education programs that emphasize the husband's involvement and workplace support.